Competition Policy and Productivity Growth: An Empirical Assessment - Paolo Buccirossi; Lorenzo Ciari; Tomaso Duso; Giancarlo Spagnolo; Cristiana Vitale (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
This paper empirically investigates the effectiveness of competition policy by estimating its impact on Total Factor Productivity (TFP) growth for 22 industries in 12 OECD countries over the period 1995-2005. We ?nd a robust positive and signi?cant effect of competition policy asmeasured by newly created indexes. We provide several arguments and results based on instrumental variables estimators as well as non-linearities to support the claim that the established link can be interpreted in a causal way. At a disaggregated level, the effect on TFP growth is particularly strong for speci?c aspects of competition policy related to its institutional setup and antitrust activities (rather than merger control). The effect is strengthened by good legal systems, suggesting complementarities between competition policy and the ef?ciency of law enforcement institutions.
urn:nbn:de:bvb:19-epub-13271-4
Keywords: 330; Competition Policy; Productivity Growth; Institutions; Deterrence; OECD; Wettbewerbspolitik; Kartellrecht; Unternehmenserfolg; Produktivität; OECD-Staaten